PENGARUH PARITAS TERHADAP PERSENTASE ESTRUS DAN KEBUNTINGAN PADA SAPI BALI YANG DISINKRONISASI ESTRUS DENGAN DUA KALI PENYUNTIKAN PROSTAGLANDIN F2α (PGF2α) - Rojab Fadillah; Sri Suharyati; Madi Hartono (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
The research aimed to: (1) determine the effect of parities on the precentage of estrous andconception of Bali cows after estrous synchronization with prostaglandin F2α (PGF2α) injectiontwice; (2) determine the best parity of Bali cows after estrous synchronization with prostaglandinF2α (PGF2α) injection twice from the various parities of Bali cows.The research was held in November until February 2013, located in Sukoharjo II Village,Sukoharjo District, Pringsewu Regency. This research used Completely Randomized Design(CRD) with three treatments and four repetitions. The treatments were Bali heifers (P0); Bali cowswhich have calved once (P1); and Bali cows which have calved twice (P2). Hormone used for thesynchronization was Juramate® with doses of 500 μg/cow or 2 ml/cow intramuscularly. Data ofpercentage of estrous and conception was analyzed by using Chi-square on significant level of 5%.The result of the research showed that estrous percentages after prostaglandin F2α (PGF2α)injection twice of Bali Cows P0, P1, P2 were 100%. The conception percentage of Bali cows P0, P1,P2 in a row were 100%; 75%; 75%. Based on the advanced test of Chi-square, parity was notsignificantly different (P>0,05) on the percentage of estrous and conception of Bali cows after theprostaglandin F2α (PGF2α) injection twice.